English Slang in “Gap Year” Movies Series - Fanny, Rahilla Fanny (JL3T (Journal of Linguistics, Literature and Language Teaching), 2020)
This research discussed about the slang words in Gap Year movie series and the word formation of the slang words which were found in the movie series. Slang itself was used by certain group or community, which could be produced by compounding, affixation, truncation, conversion, blending, neologism, etymology, borrowing, coinage, and multiple processes. This research used a qualitative method. In this research, the data were collected from Gap Year movie series in the form of British slangs.Then the data were checked by using dictionary, Oxford English Dictionaries Online and Etymology dictionaries online to make sure whether the data belonged to slang words or not and also to check the origin of the words. The data were also analyzed based on Plag and Yule’s theories in terms of etymology, borrowing, coinage, and multiple processes. After collecting the data, there were 30 slang words found in this movie series. The result of the research showed that the slangs were formed through compounding (8 data), affixation (5 data), truncation (1 data), blending (2 data), etymology (9 data), borrowing (1 data), coinage (2 data), and multiple process (2 data). Therefore, the most used of word formation process was etymology.